(untitled) (Journal Of Educational and Psychological Researches, 2024)
The research aims to identify goal orientation, cognitive refinement, and cognitive stability among middle school students. The research sample consists of 300 third-year middle school students in morning study for the academic year 2023-2024. The researcher adopted the scale of goal orientation developed by Al-Zuhairi (2013), consisting of 32 items, and developed a scale of 20 items to measure cognitive refinement and stability. The researcher used SPSS to analyze the data. The search results showed middle school students have weaknesses in goal orientations compared to the hypothesized average of the scale. In middle school, students use cognitive skills (refinement and stability) in their academic lives. There is a significant positive correlation between goal orientation and cognitive refinement for middle school students. The researcher presented some recommendations and suggestions